Estudo paramétrico da injeção de vapor em reservatórios delgados - Gurgel, Antônio Robson (2009)
Exploration of heavy oil reservoirs is increasing every year in worldwide, because the discovery of light oil reservoirs is becoming increasingly rare. This fact has stimulated the research with the purpose of becoming viable, technically and economically, the exploration of such oil reserves. In Brazil, in special in the Northeast region, there is a large amount of heavy oil reservoir, where the recovery by the so called secondary methods Water injection or gas injection is inefficient or even impracticable in some reservoirs with high viscosity oils (heavy oils). In this scenario, steam injection appears as an interesting alternative for recover of these kinds of oil reservoirs. Its main mechanism consists of oil viscosity reduction through steam injection, increasing reservoir temperature. This work presents a parametric simulation study of some operational and reservoir variables that had influence on oil recovery in thin reservoirs typically found in Brazilian Northeast Basins, that use the steam injection as improved oil recovery method. To carry out simulations, it was used the commercial software STARS (Steam, Thermal, and Advanced Processes Reservoir Simulator) from CMG (Computer Modeling Group) version 2007.11. Reservoirs variables studied were horizontal permeability, vertical and horizontal permeability ratio, water zone and pay zone thickness ratio, pay zone thickness and thermal conductivity of the rock. Whereas, operational parameters studied were distance between wells and steam injection rate. Results showed that reservoir variables that had more influence on oil recovery were horizontal permeability and water zone and pay zone thickness ratio. In relation to operational variables, results showed that short distances between wells and low steam injection rates improved oil recovery